If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5w + 6 = 16w + -3w + 54 Reorder the terms: 6 + 5w = 16w + -3w + 54 Reorder the terms: 6 + 5w = 54 + 16w + -3w Combine like terms: 16w + -3w = 13w 6 + 5w = 54 + 13w Solving 6 + 5w = 54 + 13w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-13w' to each side of the equation. 6 + 5w + -13w = 54 + 13w + -13w Combine like terms: 5w + -13w = -8w 6 + -8w = 54 + 13w + -13w Combine like terms: 13w + -13w = 0 6 + -8w = 54 + 0 6 + -8w = 54 Add '-6' to each side of the equation. 6 + -6 + -8w = 54 + -6 Combine like terms: 6 + -6 = 0 0 + -8w = 54 + -6 -8w = 54 + -6 Combine like terms: 54 + -6 = 48 -8w = 48 Divide each side by '-8'. w = -6 Simplifying w = -6
| 9y-14=6y-2 | | -3w+11=-8w+51 | | y=7x^2-4x | | 7x-5y-10=0 | | 24=-11y-8+3y | | 60*0.2= | | 3w-4=-16 | | -32=w/5-7 | | -v+131=180 | | 31=-u+184 | | 205=96-y | | -25=4u+3 | | 82-(4-6)2= | | 25n^8-49n^7-2n^6=0 | | -3+w=-4 | | -6=u-4 | | 5(2x-9)+3x=4x-18 | | 13=0.5((4x-10)+(3x+8)) | | 9x-(x+4)=2x+32 | | (1/7(x))+((1/7)x+1)+29=x | | 2x^1/2-7x^1/4+3=0 | | 63=.5h*9 | | 4x+7=54 | | 1/2*(3/5((2^3)-6))+1/5 | | 7/5x^2-7/9x-4/3x | | 1/2*3/5((2^3)-6)+1/5 | | 82x+4x=68.5 | | 5y+1/9=6y+5/9 | | 0.50x+0.05(80)=0.25(64) | | -8(x+5)+3=-37 | | 5x/14-3x/14-11x/14= | | -3x+2y+z=4 |